2020
DOI: 10.5194/nhess-20-1867-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ambient conditions prevailing during hail events in central Europe

Abstract: Abstract. Around 26 000 severe convective storm tracks between 2005 and 2014 have been estimated from 2D radar reflectivity for parts of Europe, including Germany, France, Belgium, and Luxembourg. This event set was further combined with eyewitness reports, environmental conditions, and synoptic-scale fronts based on the ERA-Interim (ECMWF Reanalysis) reanalysis. Our analyses reveal that on average about a quarter of all severe thunderstorms in the investigation area were associated with a front. Over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…Thus, the link to heavy precipitation events (including flood events) has already been intensively investigated in past years (e.g. Martius et al, 2013;Grams et al, 2014;Piaget et al, 2015;Sousa et al, 2017;Lenggenhager et al, 2018;Lenggenhager and Martius, 2019). A new study by Mohr et al (2019) shows a statistical relationship between convective activity (based on lightning data) and specific blocking situations in the European sector.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the link to heavy precipitation events (including flood events) has already been intensively investigated in past years (e.g. Martius et al, 2013;Grams et al, 2014;Piaget et al, 2015;Sousa et al, 2017;Lenggenhager et al, 2018;Lenggenhager and Martius, 2019). A new study by Mohr et al (2019) shows a statistical relationship between convective activity (based on lightning data) and specific blocking situations in the European sector.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Qiang et al [23], an FM acted on the feature extractor to solve the dilemma that high-order features in sparse data were difficult to learn while ensuring the diversity of extracted features and reducing the complexity of the algorithm. This is similar to matrix decomposition in collaborative filtering, and the expression of an FM is ( ) (5) where i v represents the latent vector of feature component i…”
Section: Fm Componentmentioning
confidence: 99%
“…In meteorology, hail is generally forecast by meteorological factor analysis and atmospheric evolution law [5]. Manzato et al [6] conducted diagnostic analysis on 52 2 of 22 meteorological factors, and the results revealed that five sounding factors had good correlation with local hail events.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-day clusters of severe weather and associated high impacts have also been reported from North America (Shafer, C., Doswell III, 2012;Trapp, 2014;Schroder and Elsner, 2020;Gensini et al, 2019). Although the atmospheric conditions associated with hail in Switzerland and central Europe are well studied (e.g., Huntrieser et al, 1997;Madonna et al, 2018;Taszarek et al, 2017;Púčik et al, 2015;Brooks, 2009;Púčik et al, 01 Nov. 2019;Kunz et al, 2020), little is known about the large-scale weather conditions that lead to multi-day clusters of hail days. Such multi-day clusters are likely the result of the extended longevity or repeated re-establishment of particular features of weather situations over Europe.…”
Section: Introductionmentioning
confidence: 97%